From Temptation to Sin: A Theological Study of Human Moral Struggles - Sugianto, Edi (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2025)
Sin has damaged human relationships with God, fellow beings, and the universe. It could only be resolved by God's grace. Even believers who have been redeemed still have the potential to fall into sin when faced with temptation. The purpose of this research is to discover and describe the pattern of human fall into sin and the efforts of believers in resisting temptation and fighting sin. This study employs a qualitative theological research method with text analysis. The findings reveal that the pattern of falling into sin begins with temptation, which enters through the five senses and is then processed by the human mind and heart. The response is subsequently expressed in thoughts, feelings, and actions. A sinful heart tends to lead a person toward sin, whereas a heart filled with God's Word is more likely to overcome trials and endure tests of faith. Therefore, believers must fill and guard their hearts with God’s Word so that their hearts, minds, and will align with His will and are reflected in actions that glorify Him.